Chapter Five: Principles of consciousness and theatre contexts. (Consciousness, Literature & the Arts (1573-2193), 2013)
Chapter five of the book "Observing Theatre Spirituality and Subjectivity in the Performing Arts" by Daniel Meyer-Dinkgräfe is presented. It discusses the principles of the contexts of consciousness and theatre and defines mass consciousness as a multi-layered complex of fields of oscillation that occur in the world and throughout the universe by many people.